Missing Link: Early Roman textiles and Norican-Pannonian female dress from Potzneusiedl, Austria - Saunderson, Kayleigh; Grömer, Karina; Formato, Lucia C. (Archaeological Textiles Review, 2022)
Cremation was the most widespread burial tradition during the Early Roman period in the provinces of Noricum and Pannonia, thus leaving a gap in the archaeological record of in situ dress components, including the textiles. In this context, the fist century CE inhumation burials from Potzneusiedl, eastern Austria, are unique, representing the only known inhumations from this period and region. Additionally, some of the women’s in situ brooches carry textile remains belonging to their clothing. Their analysis provided interesting technical and functional information. The textiles demonstrate both La Tène as well as Roman characteristics, representing a missing link between the periods. The locations and microstratigraphy of the textiles also reveal how the garments were worn, and this is comparable with the pictorial evidence on the large number of tombstones of the area from the first to second century CE.